BRIEF STRATEGIC FAMILY THERAPY KELUARGA â€œTTâ€ TERHADAP INTERAKSI SOSIAL â€œCAâ€ - Dewi Fitri Rakhmania (Politeknik Kesejahteraan Sosial Bandung, 2015)
AbstractÂ This article based on result of the research regarding application of Brief Strategic Family Therapy (BSFT) to the